2013
DOI: 10.1002/glia.22460
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes are a neural target of morphine action via glucocorticoid receptor‐dependent signaling

Abstract: Chronic opioid use leads to the structural reorganization of neuronal networks, involving genetic reprogramming in neurons and glial cells. Our previous in vivo studies have revealed that a significant fraction of the morphine-induced alterations to the striatal transcriptome included glucocorticoid (GC) receptor (GR)-dependent genes. Additional analyses suggested glial cells to be the locus of these changes. In the current study, we aimed to differentiate the direct transcriptional effects of morphine and a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 96 publications
2
48
0
1
Order By: Relevance
“…Our analyzes indicated that these systems depend on different molecular mechanisms that either predominantly use gene proximal promoters (employing SRF and CREB1 factors) or enhancer regions (GR). Moreover, it has been previously shown that these two transcriptional systems are active in different cellular compartments of the brain (Carter et al, 2012;Korostynski et al, 2013;Slezak et al, 2013). The comparison of transcriptional response to pharmacological stimuli between neurons and glia provides novel insight into the synergy in control of brain plasticity between these two compartments (Cadet and Bisagno, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our analyzes indicated that these systems depend on different molecular mechanisms that either predominantly use gene proximal promoters (employing SRF and CREB1 factors) or enhancer regions (GR). Moreover, it has been previously shown that these two transcriptional systems are active in different cellular compartments of the brain (Carter et al, 2012;Korostynski et al, 2013;Slezak et al, 2013). The comparison of transcriptional response to pharmacological stimuli between neurons and glia provides novel insight into the synergy in control of brain plasticity between these two compartments (Cadet and Bisagno, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Our results also suggest potential involvement of the transcriptional insulators, such as CTCF, in the genomic localization of GR-dependent and antidepressant-induced transcriptional alterations in the brain (Ishihara et al, 2006). The induction of a GR-regulated expression pattern in the striatum is common not only for tranylcypromine and mianserin but also for fluoxetine, tianeptine and bupropion (Korostynski et al, 2013). It has been suggested that the general physiological response of glial cells is involved in the therapeutic effect of antidepressants (Sanacora and Banasr, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 98%
See 2 more Smart Citations
“…25 While neurons engage in cross-talk with oligodendroglial cells during myelination, one study has reported limited CS effects in striatal neurons, suggesting that at least some neurons are not direct targets of CS action. 26 Such observations suggest that CS may impact myelination through indirect effects mediated by nonmyelinogenic glial cell intermediaries, but rigorous evaluation of direct effects of CS on oligodendroglia is lacking. There is heavy reliance in the field on histological observations in cultures, but the constituent cell types are often poorly characterized.…”
mentioning
confidence: 99%